Proposta de Intervenção para Auxiliar a Reabilitação Motora e Cognitiva de Pacientes com Acidente Vascular Cerebral - Moura, Daniela Maria de Sousa (2012)
Stroke is the leading cause of combined motor and cognitive disability worldwide. The rehabilitation of stroke patients is mostly directed towards motor recovery through the training of the affected member under supervision of a Physical Therapist. In the present study we introduce a new approach for both cognitive and motor therapy, which relies on motor imagery of the upper limbs and working memory training. This therapy should be utilized as an adjuvant to physical therapy. Ten individuals (5 men and 5 women) were selected for the pilot study, all of them in the acute phase of the first ischemic stroke episode. The control group had 5 individuals who were submitted to physical therapy only, whilst the other 5 patients in the experimental group also performed the cognitive and motor training with a video game specially built for this study. Two patients left the experimental group before the end. Total training lasted for 9 weeks, 2 times a week, for half an hour. Patients reported they enjoyed playing the game, even though it required a lot of mental effort, according to them. Plus, they considered it had a beneficial influence in their activities of daily living. No side effects were reported. Preliminary results suggest there is a difference between groups in cognitive and upper limb motor evaluation following the intervention. It is important to notice that our conclusions are limited due the small sample number. Overall, this work is supported by other studies in literature focused in rehabilitation with motor imagery and working memory and indicate a continuity of the research, increasing total training hours